Actuator fault tolerance in control systems with predictive constrained set-point optimizers - Marusak, Piotr M.; Tatjewski, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
Mechanisms of fault tolerance to actuator faults in a control structure with a predictive constrained set-point optimizer are proposed. The structure considered consists of a basic feedback control layer and a local supervisory set-point optimizer which executes as frequently as the feedback controllers do with the aim to recalculate the set-points both for constraint feasibility and economic performance.
Keywords: fault-tolerant control; model predictive control; set-point optimization; nonlinear systems